Toxic mechanism of nickel exposure on cardiac tissue - Novelli, E. L. B. [UNESP]; Diniz, Y. S. [UNESP]; Machado, T. [UNESP]; Proença, V. [UNESP]; Tibiriçá, T. [UNESP]; Faine, L. [UNESP]; Ribas, B. O.; Almeida, J. A. [UNESP] (My University, 2000)
The incidence of cardiovascular disease has increased in the general population, and cardiac damage is indicated as one important cause of mortality. In addition, pollution and metal exposure have increased in recent years. For this reason, toxic effects of metals, such as nickel, and their relation to cardiac damage should be urgently established. Although free radical-mediated cellular damage and reactive oxygen species have been theorized as contributing to the nickel mechanism of toxicity, recent investigations have established that free radicals may be important contributors to cardiac dysfunction. However, there is little information on the effect of nickel exposure on markers of oxidative stress in cardiac tissue. Nickel exposure (Ni2+ 100 mg L-1 from NiSO4) significantly increased lipoperoxide and total lipid concentrations in cardiac tissue. We also observed increased serum levels of cholesterol (59%), lactate dehydrogenase (LDH-64%), and alanine transaminase (ALT-30%) in study animals. The biochemical parameters recovered to the control values with tocopherol intake (0.2 mg 200 g-1). Vitamin E alone significantly decreased the lipoperoxide concentration and increased superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in the heart. Since no alterations were observed in catalase and GSH-Px activities by nickel exposure while SOD activities were decreased, we conclude that superoxide radical (O2 -) generated by nickel exposure is of primary importance in the pathogenesis of cardiac damage. Tocopherol, by its antioxidant activity, decreased the toxic effects of nickel exposure on heart of rats.
Keywords: Enzymes; Heart; Nickel; Oxidative stress; Pollution; Tocopherol; alanine aminotransferase; catalase; cholesterol; free radical; glutathione peroxidase; lactate dehydrogenase; lipid peroxide; nickel; reactive oxygen metabolite; superoxide dismutase; tocopherol; animal cell; animal experiment; animal model; animal tissue; antioxidant activity; cardiotoxicity; cardiovascular disease; cell membrane; controlled study; enzyme activity; lipid peroxidation; male; mortality; nonhuman; oxidative stress; pathogenesis; rat; water contamination; water pollution; Animalia